2019
DOI: 10.5588/pha.18.0062
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in children treated for tuberculosis with the new dispersible fixed-dose combinations in Port Moresby

Abstract: The new child-friendly fixed dose combinations (FDCs) were introduced at Port Moresby General Hospital, Papua New Guinea, in 2016 for the first-line treatment of children (aged 15 years) with tuberculosis (TB) who weighed 25 kg. Objective: To describe the characteristics and outcomes for children treated with the new FDCs, and to identify risk factors for unfavourable treatment outcomes. Design: This was a retrospective cohort study of all children treated for TB with the FDCs from August 2016 to August 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…A TPT regimen of 3 months of daily rifampicin and isoniazid (3RH)recommended by WHO in 2018has been associated with high uptake, completion and safety in young child contacts under programmatic conditions in resource-limited settings (18). The availability in PNG of dispersible, child-friendly combined formulations for active TB since 2016 (19), led to the successful implementation of 3RH for young child contacts of DS-TB in Daru from 2019. In Daru, up to 20% of incident TB is MDR/RR-TB (5).…”
Section: Tb Preventive Treatmentmentioning
confidence: 99%
“…A TPT regimen of 3 months of daily rifampicin and isoniazid (3RH)recommended by WHO in 2018has been associated with high uptake, completion and safety in young child contacts under programmatic conditions in resource-limited settings (18). The availability in PNG of dispersible, child-friendly combined formulations for active TB since 2016 (19), led to the successful implementation of 3RH for young child contacts of DS-TB in Daru from 2019. In Daru, up to 20% of incident TB is MDR/RR-TB (5).…”
Section: Tb Preventive Treatmentmentioning
confidence: 99%
“…Except for the National Capital District, provinces in PNG do not have specific clinics to follow up child TB, and caregivers are not properly supported. PNG was one of the first countries to introduce child-friendly fixed-dose formulations to improve treatment in young children managed at Port Moresby General Hospital [65]. Recent progress has also been seen in both diagnosis and treatment of child TB in Port Moresby, under a TB/HIV project which supports additional child TB focused human resources, tools, training and transport.…”
Section: Papua New Guinea: Addressing Challenges In a High-burden Chi...mentioning
confidence: 99%
“…To date, commonly used pharmaceutical formulations are either liquid dosage forms (e.g., solutions, suspensions), fixed dose dispersible tablets and in most instances, adult tablets are often broken, crushed or mixed with food or water (co-administration) to make pediatric management possible [12][13][14][15]. Despite the availability of a few commercialized pediatric preparations, considerable global scarcity still exists, meaning that many children are unable to access these medicines [15][16][17][18][19]. Moreover, studies have shown that co-administration (with food, water etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies show that the most popular age appropriate delivery systems are small sized, solid oral drug delivery systems e.g., minitablets and multi-particulates and orally disintegrating formulations like orodispersible tablets or films [18,25]. Particularly, orodispersible formulations are of choice because of their characteristic advantages such as water free administration, easy to use anywhere and at any time without the need for external help or specialized caregivers, improved stability, easier transportation, cost effectiveness and rapid disintegration when placed within the oral cavity releasing incorporated API for absorption.…”
Section: Introductionmentioning
confidence: 99%